Pengaruh Model Pembelajaran Berbasis Masalah dengan Pendekatan STEM terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Ripaldo Pandiangan; Asrin Lubis (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to determine whether there is an influence of the problem-based learning model (PBL) with a STEM approach on the mathematical problem solving ability of grade VIII students of SMP Negeri 17 Medan. This research was conducted at SMP N 17 Medan T.A 2023/2024. The research method used is a quasi-experimental method. The sample of this study consisted of two classes, namely class VIII-3 as an experimental class taught with a PBL model with a STEM approach and class VIII-4 as a control class taught with conventional models. Based on descriptive statistics and categorization of research results, it was found that the mathematical problem solving ability of experimental class students was 67,74% of students in the high category, 32.26% of other students in the medium category, and no students in the low category. Meanwhile, in the control class, 15,63% of students were in the high level of problem solving ability, 53,13% were in the medium level and 31,24% of students were in the category low category. Thus it can be seen that the mathematical problem solving ability of grade students taught with PBL with a STEM approach is better than conventional learning models. Furthermore, with inferential statistical analysis for the t test, calculated t value = 2,42 and ttable = 1,999623, thus t calculated > t table means that the problem-solving ability of students taught with PBL with a STEM approach is not the same as students who use the learning conventional model. With further analysis, Fcalculated = 5,6847 and F table = 3,998494482, then calculated F > F table so it can be concluded that problem-based learning models with a STEM approach have a significant effect on students' mathematical problem solving abilities.